Safety of elexacaftor/tezacaftor/ivacaftor dose reduction: Mechanistic exploration through physiologically based pharmacokinetic modeling and a clinical case series. Issue 4 (12th March 2023) - Hong, Eunjin; Li, Regina; Shi, Alan; Almond, Lisa M.; Wang, Joshua; Khudari, Amin Z.; Haddad, Soumar; Sislyan, Sarkis; Angelich, Marissa; Chung, Peter S.; Rao, Adupa P.; Beringer, Paul M.
Abstract: Introduction: Elexacaftor/tezacaftor/ivacaftor (ETI) treatment is associated with significant improvement in lung function in people with cystic fibrosis (pwCF); however, some patients experience adverse effects (AEs) including hepatotoxicity. One potential strategy is dose reduction in ETI with the goal of maintaining therapeutic efficacy while resolving AEs. We report our experience of dose reduction in individuals who experienced AEs following ETI therapy. We provide mechanistic support for ETI dose reduction by exploring predicted lung exposures and underlying pharmacokinetics–pharmacodynamics (PK‐PD) relationships. Method: Adults prescribed ETI who underwent dose reduction due to the AEs were included in this case series, and their percent predicted forced expiratory volume in 1 s (ppFEV1 ) and self‐reported respiratory symptoms were collected. The full physiologically based pharmacokinetic (PBPK) models of ETI were developed incorporating physiological information and drug‐dependent parameters. The models were validated against available pharmacokinetic and dose–response relationship data. The models were then used to predict lung concentrations of ETI at steady‐state. Results: Fifteen patients underwent dose reduction in ETI due to AEs. Clinical stability without significant changes in ppFEV1 after dose reduction was observed in all patients. Resolution or improvement of AEs occurred in 13 of the 15 cases. The model‐predicted lung concentrations of reduced dose ETI exceeded the reported half maximal effective concentration (EC50 ) from measurement of in vitro chloride transport, providing a hypothesis as to why therapeutic efficacy was maintained. Conclusion: Albeit in a small number of patients, this study provides evidence that reduced ETI doses in pwCF who have experienced AEs may be effective. The PBPK models enable exploration of a mechanistic basis for this finding by simulating target tissue concentrations of ETI that can be compared with drug efficacy in vitro .